Exploration and Optimization of Potential Fungi to Degrade Herbicides with Active Ingredient Isopropylamine Glyphosate from Shallot Plantations by In Vitro - Karim, Hilda; Sahribulan, Sahribulan; Adawiyah, Rhidoyatul (The University of Lampung, 2024)
This research was conducted by isolating potential fungi from soil samples exposed the herbicides with the active ingredient of isopropylamine glyphosate (IAG) and then testing the degradation ability of the obtained fungal isolates. The results showed 15 isolates fungi obtained from the soil to a depth of 10 cm including Aspergillus sp. with black, green and yellow colonies, Cladosporium sp., Penicillum sp., Rhizopus sp., Mucor sp., Cephalosporium sp., Phymatotrichum sp., Pytopthora sp., Curvularia sp., Microsporum sp., Colletothricum sp., Acremonium sp., Tricophyton sp. and 4 isolates from soil samples with a depth of 20 cm, namely Chrysosporium sp., Geotrichum sp., Aspergillus sp. with black and green colonies. However, after testing for the presence of herbicides with concentrations of 10 ppm, 20 ppm, and 30 ppm, only 2 isolates were able to survive, namely Aspergillus sp with black and green colonies. Further testing on the ability to degrade the IAG was found to reduce the concentration of herbicide. The optimum biodegradability to IAG of Aspergillus sp. green and black found in P20 (20 ppm) treatment at the 5th day of incubation, namely 98.69 ppm for Aspergillus sp. green, and 96.11 ppm for Aspergillus sp. black. Keywords: Aspergillus sp., Biodegradation, Fungi, Herbicide, Isoprofile amine glyphosate.